2019
DOI: 10.1002/ps.5540
|View full text |Cite
|
Sign up to set email alerts
|

Production of pyrrolizidine alkaloids and shikonins in Echium plantagineum L. in response to various plant stressors

Abstract: Background Echium plantagineum, a native of Europe and Africa, is a noxious invasive weed in Australia forming monocultural stands in pastures and rangelands. It produces a complex mixture of bioactive secondary metabolites, including toxic pyrrolizidine alkaloids (PAs), that protect the plant from insect and livestock herbivory and naphthoquinones (NQs), which suppress competition from weeds, insects and pathogens, and also influence invasion success. However, the extent to which allelochemical production is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Second, PA synthesis is dependent on developmental stage and thus on the season of harvest, shown in a study from Italy presenting an average PA content of plants of 0.33% of dry weight over the growing season, in which the highest PA levels, of around 1%, were found in the young sprouts and flower heads [ 164 ], whereas another study showed increased total amounts of PAs during plant development, correlating with an increase in biomass at nearly constant PA concentrations [ 39 ]. More specifically, the highest PA concentrations ranged from 3.2 to 6.6 g/kg dry weight and were found in plants from the beginning of July until the middle of October when the rainy season begins [ 165 ], findings that are in line with increased PA concentrations in plants under drought conditions [ 166 , 167 ]. PA production in plants was reduced under the use of nutrients such as NBK (nitrogen, phosphorus, and potassium) fertilizers, which are complete fertilizers [ 168 ].…”
Section: Principles Of Plant Pa Biosynthesismentioning
confidence: 99%
“…Second, PA synthesis is dependent on developmental stage and thus on the season of harvest, shown in a study from Italy presenting an average PA content of plants of 0.33% of dry weight over the growing season, in which the highest PA levels, of around 1%, were found in the young sprouts and flower heads [ 164 ], whereas another study showed increased total amounts of PAs during plant development, correlating with an increase in biomass at nearly constant PA concentrations [ 39 ]. More specifically, the highest PA concentrations ranged from 3.2 to 6.6 g/kg dry weight and were found in plants from the beginning of July until the middle of October when the rainy season begins [ 165 ], findings that are in line with increased PA concentrations in plants under drought conditions [ 166 , 167 ]. PA production in plants was reduced under the use of nutrients such as NBK (nitrogen, phosphorus, and potassium) fertilizers, which are complete fertilizers [ 168 ].…”
Section: Principles Of Plant Pa Biosynthesismentioning
confidence: 99%
“…Recent studies were performed to elucidate the shikonin production pathway and its regulation in planta . For example, Skoneczny et al (2019) used a metabolomic approach, profiling naphthoquinones and pyrrolizidine alkaloids and demonstrated the influence of high temperature and water withholding on the accumulation of A/Sd, especially deoxyshikonin, in Echium plantagineum . Similarly, shikonin derivatives were shown to accumulate over time in Echium spp.…”
Section: Introductionmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved variation in soil nutrients (Effah et al, 2020) Chromolaena odorata Odoratin Higher amounts of odoratin in non- (Tharayil et al, 2009) Datura stramonium (native Atropine and scopolamine Greater amounts of two compounds in to Mexico; invasive in Spain) native range than in non-native range owing to presence of specialist herbivores (Castillo et al, 2019) Echium plantagineum Naphthoquinones and Defend against insect and (native to Europe and Asia; pyrrolizidine alkaloids livestock herbivory, competitive invasive in Australia) advantages against weeds (Skoneczny et al, 2019).…”
Section: Accepted Articlementioning
confidence: 99%